Fraud Resistant Off-Line Card Micropayments Using FRoDO and PUF (International Journal of Innovative Research in Engineering & Management, 2023)
The internet payment system, which is a  widespread cybercrime, is a major issue nowadays. Attackers  concentrate on point of sale (POS) systems, the point at which  a bank or merchant initially obtains customer information,  with the goal of stealing confidential customer information.  Effective computer systems with a card reader and specialised  software are POS architectures. In this situation, the attacker  might utilise malicious software (MS) to steal card statistics.  If the customer and the supplier are consistently cut off from  the network in, no online payment is practical. If the  community fails, attacker's side will attempt to steal the  password from the users throughout the price, therefore a safe  online transaction price may not be achievable. Due to the  PoS information breaches, we recommend an offline micro fee solution that is secure and protects privacy for the  persistent attackers in our paper. We use the FRoDO protocol  to make the payment simple and secure from attackers. This  protocol not only checks the client's coins but also confirms  the client's identity by using identification details. This  protocol increases flexibility and security and boosts the  device's efficiency by infusing a comfortable micro-charge  between the client and carrier.
Keywords: POS systems; Malicious Software; Micro fee solution and FRoDO